Análisis de necesidades educativas curriculares en la educación primaria dirigida a niños (as) nicaragüenses migrantes en Costa Rica - Nidia Esperanza Mejía-Arias (Universidad Nacional, Costa Rica, 2008)
The intention of the article is to announce the needs of a curriculum Identified in the Nicaraguan migrant children that study at the rural primary school "Los Angeles" in the location of Los Chiles Costa Rica. They actually are in an exclusion, discrimination and indifference situation from the local institutions. There are strong obstacles for the effective learning and development of positive attitudes, lack of responsible participation of the educative community; the methodological procedure used at the classrooms and the curricular adjustment at the pedagogical official model from Costa Rica, divorced those, from the sociocultural conditions of the children, their families and the rural community where they live. This situation affects the children motivation, for not achieve educational goals, the few that register at primary school doesn´t end it and those that complete it have academic difficulties to enter at high school. The time has come for the educational systems from both countries -Nicaragua and Costa Rica- to consider joint educational strategies that can give an answer to the educational curricular needs that the Nicaraguan migrant children presents at the rural schools in Costa Rica.